Mapping Research Topics Regarding Resolving Sharia Economic Disputes: Bibliometric Analysis Study - Elfi Sahara (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
The Sharia economic dispute in Indonesia is growing along with the rise of Sharia-based economic activities. This significant growth is followed by an increase in non-performing loans and the potential for an increase in sharia economic disputes submitted to religious courts. The research aims to map research topics on sharia economic disputes. This research uses a bibliometric method using bibliographic data with the VOSviwer application tool to analyze research trends and scientific patterns. This research obtained secondary data through a Google Scholar search on the Publish or Perish application. The results show research development in Sharia economic disputes in 2018-2023 from the publish or perish application on Google Scholar indexed search with the highest number of article publications in 2023, namely 51. Meanwhile, the most related scientific publication is the Journal of Islamic Business Law. Furthermore, the most productive writer's productivity for 2018-2023 was Fuadi S, with 4 articles published.